PENGARUH PELATIHAN TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN DENGAN MEDIATOR STRES KERJA (STUDI PADA UD. LADANG ROTI-BRAUD ARTISAN BAKERY DENPASAR) - Agung Paramartha, Ida Bagus; Sintaasih, Desak Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023, 2023)
Organizational commitment is the involvement and dedication of employees to accept organizational goals and employees' willingness to participate in all organizational activities towards improvement. This study aims to analyze the effect of training on employee organizational commitment with job stress as a mediator. This research was conducted at UD. Ladang Roti, with 37 employees as respondents, and the sampling technique used is the saturated sample technique which is analyzed by path analysis technique. The results of this study indicate that training has a positive and significant effect on employee organizational commitment, training has a negative and significant effect on employee work stress, and work stress has a negative and significant effect on employee organizational commitment. From the results of testing the mediator variable, it is proven that work stress significantly mediates the effect of training on employee organizational commitment. Training is important given to employees because it can reduce work stress levels which can ultimately increase employee commitment to the company.